(untitled) (Journal of Student Affairs in Africa, 2026)
The demand for housing among university students has increased in proportion to the global surge in university enrolment. Students heavily depend on private housing alternatives since university-provided housing facilities cannot accommodate the increasing student population. There is a lack of research on how homeowner behaviours affect the academic outcomes of university students. This case study examines the impacts of homeowner behaviours on the academic performance of students at the University of Cape Coast (UCC) in Ghana. A single case study was chosen, and four main communities were purposively selected, namely: Kwapro, Amamoma, Apewosika, and Duakor. Focus group discussions were organised in each of the selected communities for data collection. The data were analysed thematically. The study’s results showed that the academic performance of students at the University of Cape, Ghana is impacted by the following five homeowner behaviours: (1) regular rent increases; (2) delays in maintenance; (3) room overcrowding; (4) stringent gate locking; and (5) frequent noise-making. These behaviours seem to have a psychological impact, cause financial burden, interrupt learning, and decrease study periods. The study recommends collaboration among key stakeholders (UCC Student representatives, homeowners, rent control regulators, and the Office of Student Affairs, UCC) to establish frameworks to provide conducive housing options that centre the wellbeing of university students.